Factor IX-Inhibitors - Lechner, K (Thrombosis and Haemostasis, 1971)
1. Two patients with severe hemophilia B and an acquired inhibitor against factor IX are described.2. The inhibitors inactivate factor IX irreversibly. The speed of inactivation is very fast and cannot slowed down by dilution of the inhibitor or by lowering of the incubation temperature. Factor IX of serum is inactivated to a higher degree than factor IX of plasma. Factor IX inhibitors are more sensitive to dilution than factor VIII inhibitors.3. The inhibitor protein is eluted from the Sephadex G-200 column with the G-peak. On Chromatography on DEAE-cellulose two activity peaks are obtained.4. Immunologically the inhibitors belong predominantly to the immune globulins of the G-class, but it cannot be excluded that the activity is also associated with IgA. As light chains kappa chains were found in one case.